Poetic thinking and teaching. Issue 5 (3rd September 2022) - Galea, Simone
ABSTRACT: This paper discusses the relation between the poetic and teaching. Drawing on Heidegger's question of Being and his turn to poetry as the site through which Being is brought forth through an interplay between revealing and concealing, I address the intricacies of poetic thinking in teaching. I argue that thinking 'about' teaching needs to go beyond the calculative frames of reflection, prevalent in practices of teaching today. I refer to three poems to explain the deeper modes of thinking that emerge from poetry and how these can inform teaching in a manner that releases students' openness to learn and teachers' meditation on what confers their being in teaching. I conceive teachers' work as poesis, pointing to their responsibility to attend to the call of thinking as beings who 'occasion' relations with/in the world in the advents of being and becoming.